Evaluating antibacterial efficacy of extracts from Ludwigia hyssopifolia against pathogenic bacteria - Uyen To Pham; Y Thi Nhu Hoang; Bao Le (Ho Chi Minh City Open University Journal of Science - Engineering and Technology)
Ludwigia hyssopifolia extracts have historically been consumed as a healthful drink and rich in biomass. Therefore, the aims of this study were to determine the most effective fractionated extracts of L. hyssopifolia against pathogens. The whole plants of L. hyssopifolia were extracted various fractions with methanol, hexane, chloroform, ethyl acetate, and aqueous. The total phenolics and flavonoids was screened using quantitative approaches. The extracts tested for antibacterial activity against pathogens, including Bacillus cereus, Staphylococcus aureus, Escherichia coli, Salmonella Typhi, and Helicobacter pylori through the agar diffusion technique and the microtiter broth dilution method. The largest yield was obtained from the aqueous fractional extract. The phytochemical composition discovered in ethyl acetate was more abundant in phenolics and flavonoid compounds. Fractionation enhanced the antibacterial effect of the extract. The extracts showed a broad spectrum of antibacterial activity against all the bacteria tested, particularly H. pylori. In parallel, ethyl acetate extract showed antibacterial activity. The current results could provide rational support for the traditional use of L. hyssopifolia to treat infectious diseases and provide data for developing natural products.